Identity development and online and offline prosocial behaviors among early and middle adolescents - Iwasa, Yasuhiro; Hihara, Shogo; Ishizaki, Kazuya; Yasui, Genki; Hiro, Makoto; Sugimura, Kazumi (Frontiers in Psychology, 2023)
Research has demonstrated that adolescents of the digital age engage in developmental tasks by interacting with others in both online and offline environments. However, no studies have investigated how adolescents develop their identity, a crucial developmental task, by engaging in online and offline prosocial behaviors. To address this research gap, we examined the role of online and offline prosocial behavior in identity development during adolescence using variable- and person-centered approaches. The participants were 608 individuals in early adolescence (50.2% girls; age range = 12–13 years, Mage = 12.75 years, SD = 0.43) and 594 individuals in middle adolescence (50.3% girls; age range = 15–16 years, Mage = 15.79 years, SD = 0.41) in Japan. They completed questionnaires to measure identity development, online and offline prosocial behavior, and demographic characteristics. The results from the variable-centered approach (i.e., identity dimensions) revealed that both online and offline prosocial behaviors were positively related to commitments and proactive explorations in early and middle adolescence. The findings from the person-centered approach (i.e., identity statuses) demonstrated that early and middle adolescents with higher levels of online prosocial behavior were more likely to show searching moratorium than all other identity statuses, whereas those with higher levels of offline prosocial behavior were more likely to show achievement than troubled diffusion, carefree diffusion, and undifferentiated. Consistent with both variable- and person-centered approaches, these findings highlight that online prosocial behavior can be a new resource for identity development in adolescence. Moreover, the results suggest that online prosocial behaviors lead to identity status in the process of maturing identity and that offline prosocial behavior is necessary to become more mature identity status. Regarding practical implications, educating adolescents on digital media literacy, including supportive behavior in online environments, is crucial to gradually exploring their identity. In addition, for adolescents to develop more mature identity, adults should create in-person environments in which they participate in offline prosocial behavior. The limitations of our findings with respect to the online and offline prosocial behavior scale items are discussed.